PERBEDAAN TINGKAT SIMTOM ANSIETAS DAN DEPRESI ANTARA PEKERJA SEKS KOMERSIAL YANG MENDERITA HIV/ AIDS DENGAN YANG TIDAK MENDERITA HIV/ AIDS - Rini Gusya Liza; Elmeida Effendy; Freddy Subastian (Faculty of Medicine, Universitas Andalas, 2014)
AbstrakPenelitian ini bertujuan untuk mengetahui perbedaan tingkat simtom ansietas dan depresi antara pekerja seks komersial (PSK) yang menderita HIV/ AIDS dengan yang tidak menderita HIV/ AIDS. Penelitian potong lintang, dengan nonprobability sampling, jenis cluster sampling. Tempat penelitian adalah di lokalisasi Kabupaten Bengkalis dan di klinik VCT RSUD Kecamatan Mandau, Kabupaten Bengkalis. Subjek penelitian adalah wanita yang bekerja sebagai PSK di lokalisasi PSK, kooperatif, bersedia diwawancara. Subjek berjumlah 96 orang PSK; 48 orang menderita HIV/ AIDS dan 48 tidak menderita HIV/ AIDS. Data tentang status HIV/ AIDS diambil dari laporan klinik VCT RSUD Kecamatan Mandau. Alat ukur yang digunakan adalah Hospital Anxiety and Depression Scale. Analisis data yang digunakan adalah uji Kolmogorov-Smirnov. Didapatkan proporsi ansietas pada seluruh PSK adalah 22.9%, pada PSK yang menderita HIV/ AIDS 31.2% dan PSK tidak menderita HIV/ AIDS 14.6%, sedangkan proporsi depresi pada seluruh PSK adalah 25%, pada PSK yang menderita HIV/ AIDS 27.1% dan PSK yang tidak menderita HIV/ AIDS 22.9%. Tidak terdapat perbedaan yang bermakna tingkat simtom ansietas dan depresi antara pekerja seks komersial yang menderita HIV/ AIDS dengan yang tidak menderita HIV/ AIDS. Simpulan, didapatkan tingginya ansietas dan depresi pada keseluruhan PSK itu sendiri. Disamping menjadi seorang PSK ditambah lagi dengan menderita HIV/ AIDS akan menambah beratnya simtom ansietas dan depresinya.AbstractThe aims of this study is to determine the differences of anxiety and depression symptoms level between commercial sex workers who suffer HIV/AIDS with not suffer HIV/AIDS.Cross sectional study, using nonprobability sampling technique, the type is cluster sampling. Location is in red light district of commercial sex workers in Kabupaten Bengkalis and in VCT clinic of general hospital of Kecamatan Mandau Kabupaten Bengkalis. Subjects were women who worked as prostitutes in red light district, cooperative, willing to be interviewed. Sample size were 96 women, 48 suffer HIV/ AIDS and 48 not suffer HIV/AIDS. Data on HIV/ AIDS status are collected from the report of VCT clinic of general hospital of Kecamatan Mandau. Measuring instruments is the Hospital Anxiety and Depression Scale. Data analysis by using the Kolmogorov-Smirnov test. It was found the proportion of anxiety in all sex workers is 22.9%, in sex workers who suffer HIV/ AIDS is 31.2% and in sex workers who not suffer HIV/ AIDS is 14.6%. While the proportion of depression in all sex workers is 25%, in sex workers who suffer HIV/ AIDS is 27.1% and in sex workers who not suffer HIV/ AIDS is 22.9%. There was no significant differences the level of anxiety and depression symptoms between commercial sex workers who suffer HIV/ AIDS with not suffer HIV/ AIDS. In conclusion, we get the high proportion of anxiety and depression symptoms among commercial sex workers themselves. Beside to being a prostitute in addition to having HIV / AIDS will increase the severity of symptoms of anxiety and depression.